Distributed Robust Secondary Controller for Voltage Balancing and Proportional Load Sharing in Uncertain DC Microgrids - Juwon Lee; Juhoon Back (IEEE Access, 2024)
In this paper, we present a distributed robust controller for current sharing and voltage balancing in uncertain DC microgrids. DC microgrids considered in this paper are composed of distributed generation units (DGUs), power lines, and ZI (constant impedance and constant current) loads. It is assumed that the parameters of electric components and those associated to electric and communication network are unknown but belong to known bounded sets. The proposed controller is composed of a robust primary controller and consensus-based secondary controller. The primary controller is a disturbance observer-based voltage stabilizer. It provides robustness against parameter uncertainties and ensures that DGUs under this controller have a desired behavior or dynamics. The secondary controller is a consensus-based controller that generates a reference for the primary controller. It has a distributed structure in the sense that they make decisions by communicating with local neighbors. In addition, it provides a stability condition for the primary control loop to ensure the stability of the whole closed-loop system. A rigorous stability analysis and a constructive design procedure for control parameters are provided. Finally, experiments on a lab-scale microgrid are conducted to validate the proposed controller.